(untitled) (The Lumbini Journal of Business and Economics, 2022)
This study aims to achieve the key objectives of the factors affecting the demand for life insurance in Kapilvastu district. It is a novel study in the field of the insurance industry in the context of Kapilvastu district, as this study incorporates socio-demographic variables, saving motives, and financial literacy as a determinant of demand for life insurance. Primary data has been collected through convenience sampling from a sample of 384 individuals; the study has analyzed the influence of socio-demographic variables, saving motives, and financial literacy on life insurance demand. To determine the relationship between the demographic factors and life insurance demand way ANOVA tests have been conducted. Similarly, to test the association between categorical variables chi-square test has been used. The relationship between financial literacy and saving motives (precautionary, bequest, life cycle, and wealth accumulation motives) with life insurance demand is then analyzed using multiple regression. Results have confirmed that among all the socio-demographic variables, the number of dependents, level of education, and level of income have a significant effect on the demand for life insurance. Similarly, bequest motives and financial literacy were positive contributors to life insurance policy demand. However, it is worth noting that although marital status has an insignificant effect on life insurance policy demand but unmarried individuals still tend to have more life insurance in comparison to married and widowed respondents. Other determinants of saving motives like precautionary motives, life cycle motives, and wealth accumulation motives have an insignificant effect on life insurance demand.